Russia's Fiscal Gap - Eugene Goryunov; Marija Kazakova; Laurence J. Kotlikoff; Arseny Mamedov; Kristina Nesterova; Vladimir Nazarov; Elena Grisina; Pavel V. Trunin; Alexey Shpenev (NBER, 2013)
Every country faces what economists call an intertemporal (across time) budget constraint, which requires that its government's future expenditures, including the servicing of its outstanding official debt, be covered by its government's future receipts when measured in present value. The difference between the present value of a country's future expenditures and its future receipts is called its fiscal gap. This study estimates Russia's 2013 fiscal gap at 890 trillion rubles or 28 trillion. This longterm budget shortfall is 8.4 percent of the present value of projected GDP. Consequently, eliminating Russia's fiscal gap on a smooth basis requires fiscal tightening by 8.4 percent of each future year's projected GDP. One means of doing this is to immediately and permanently raise all Russian taxes by 29 percent. Another is to immediately and permanently cut all spending, apart from servicing outstanding debt, by 22.4 percent. How can a country with vast energy resources and foreign reserves and other financial assets that exceed its official debt still have very major fiscal problems? The answer is that the Russia's energy resources are finite, whereas its expenditure needs are not. Moreover, Russia is aging and facing massive obligations from its pension system and other age related expenditures.
Keywords: 330; fiscal gap; Russia